Critical Thinking Technology in Russian Language Classes - Ashirmatova Manzura Jumanbayevna (Genius Journals, 2022)
This article provides information on critical thinking, critical thinking technologies in Russian language classes.
Keywords: Traditional lessons; critical thinking; information; education